Incidence of Maruca vitrata f. on cowpea in the sudano-sahelian zone of Niger - Zakari, O.A.; Baoua, I.; Amadou, L.; Dannon, E.; Tamo, Manuele; Mahamane, S.; Pittendrigh, B.R. (Diva Enterprises Private Limited, 2019)
The incidence of the key insect pest of cowpea (Vigna unguiculata L. Walp), the legume pod borer Maruca vitrata F., was investigated with light trap in the Sudano-Sahelian zone of Niger in 2014 and 2015. The results revealed that the first larvae appeared in August (0.03 ± 0.03 to 2.48 ± 0.32 larvae/flower and pod, respectively). Incidence varied between the seasons, and the yield losses were 20.25% in 2014 and 82.32% in 2015, when there was 435 and 496 mm total rainfall, respectively. Lifecycle in the laboratory revealed a duration of 26.42 ±0.14 days, with females living for 16.38 ± 0.56 days with fecundity of 599.74 eggs.